First total OH reactivity emission measurements from a Nordic wetland - Schallhart, Simon; Praplan, Arnaud P.; Tykkä, Toni; Reijrink, Nina; Williams, Jonathan; Hakola, Hannele; Hellén, Heidi (Finnish Environment Institute, 2023)
Volatile organic compounds (VOCs) are ever-present compounds in the air we breathe. They are emitted by natural and anthropogenic sources and are modified by atmospheric oxidants. VOCs affect air quality and human health, form and grow aerosol particles, and can impact Earth's radiative balance. Total hydroxyl radical (OH) reactivity measurements are a valuable tool for assessing the comprehensiveness of measured VOCs and can give valuable insights into in situ atmospheric chemistry. Especially in remote forested environments, missing or unaccounted for reactivity has been substantial, caused by either unmeasured primary emissions or secondary oxidation products. This study presents OH reactivity and VOC measurements over a Nordic, subarctic wetland in summer. Over half of the OH reactivity from emissions could not be attributed, while the remaining measured fraction is dominated by isoprene (42%), followed by sesquiterpenes (3%).